ANALISIS PERAN GANDA DAN STRATEGI PEMBERDAYAAN JANDA YANG BEKERJA (Studi Empiris Derah Pesisir di Kota Semarang) - Valentine S., Rizky Wilfrida; Susilowati, Indah (Diponegoro Journal of Economics, 2013)
This study examines the role of widows in the coastal area of Semarang city. Widows were low in education level and limited economic access are found in the study area. They obtained survive to fight for their household economy limitation. The objectives of the study are to determine the role of the widows with low income level who are responsible to finance their households. Besides that, this study have objective to formulate the strategies of their empowerment. This study employed mixed method of combination between qualitative and quantitative approach to analyze the data. Snowballing sampling had has been involved to select the informants while purposive sampling was applied to select 100 respondents (widows) in the study area. The descriptive statistics and triangulation were used as the tools of analysis for this study. The results found that the level of powerment in economic, political, and social access were far from complete. The study outline the strategy to empower those widows through improving the productivity of respondents, extention the education access, provide trining to improve their skills and family advocation management.